The rose and the ring or, The history of Prince Giglio and Prince Bulbo; a fire-side pantomime for great and small children. - Thackeray, William Makepeace 1811-1863 (Puffin Books, 1964)
Relates the misadventures that befell the court of Paflagonia when the Fairy Blackstick cast her magic spells.